Research on the Optimal Scheduling of Electric Vehicles in Distribute Network Based on Cluster Thought - Liu, Zhijian; Wang, Zizhuo; Li, Pengcheng; Dai, Jing; Chen, Jikai; Xu, Zhisong; Tao, Yunxu (2023 IEEE International Conference on Power Science and Technology (ICPST), 2023)
In this paper makes the following research aiming at the charging and discharging power of electric vehicles(EVs). Firstly, a large number of EVs are integrated by means of clustering based on a comprehensive consideration of EV charging-discharging characteristics. Second, the EV cluster charging-discharging power and battery capacity constraints at each moment are solved and the EV cluster boundary conditions are constructed. After that, an optimization model with the objective of minimizing load fluctuation is constructed to optimize the power situation of the cluster at each moment. Finally, simulation work is carried out based on the IEEE 33-node system to verify the effectiveness of the proposed cluster optimization method. The simulation results show that the proposed method can reasonably allocate the total charging-discharging power of the EV cluster at each time, and then achieve the purpose of smoothing the grid load curve and improving the grid operation economy.